Haluan Negara Sebagai Pedoman Kebijakan Dasar Negara Dalam Sistem Ketatanegaraan Indonesia: Sebuah Tinjauan Filsafat Kenegaraan - Lutfil Ansori (Justicia Islamica, 2019)
This paper aims to examine the essence of the Directive Principle of State Policy in the Indonesian constitutional system with a state philosophy approach based on the state philosophy of Pancasila. The Directive Principle of State Policy has become the central issue lately, which continues to roll over as needed to realign the national development planning system in the Indonesian constitutional system. However, this issue raises pros and cons of the Directive Principle of State Policy, which is deemed incompatible with the Indonesian constitutional system after the amendment of the 1945 Constitution. Therefore, to see the Directive Principle of State Policy's compatibility with the Indonesian constitutional system needs to reclaim the essence of the Directive Principle of State Policy by exploring the original intent of term from the founders of the nation. Through the Pancasila state philosophy approach, it can be seen that there is three basic state consensus agreed upon by the founders of the nation as an effort to realize the goals of the state, called a triangle of basic state consensus. They are Pancasila as the basis of the state philosophy (philosofische grondslag), the 1945 Constitution of the Republic of Indonesia as fundamental state law, and the Directive Principle of State Policy as a guideline for the state's fundamental policies. The Directive Principle of State Policy's essential element is directive principles as a guideline that directs a state policy or a guiding principle in describing the state philosophy and the mandate of the constitution into state development policies and legislation.Tulisan ini bertujuan untuk menelaah hakikat Haluan Negara dalam sistem ketatanegaraan Indonesia dengan pendekatan filsafat kenegaraan, dengan berbasis pada filsafat kenegaraan Pancasila. Haluan Negara menjadi tema sentral akhir-akhir ini yang terus bergulir seiring kebutuhan akan penataan kembali sistem perencanaan pembangunan nasional dalam sistem ketatanegaraan Indonesia. Namun keberadaannya menuai pro kontra yang dirasa tidak sesuai dengan sistem ketatanegaraan Indonesia pasca amandemen UUD 1945. Karena itu, untuk melihat ketersesuian Haluan Negara dengan sistem ketatanegaraan Indonesia perlu didudukkan kembali hakikat Haluan Negara dengan menggali maksud (original intent) Haluan Negara dari para pendiri bangsa. Melalui pendekatan filsafat kenegaraan Pancasila dapat diketahui bahwa terdapat tiga konsensus dasar yang disepakati oleh para pendiri bangsa sebagai upaya untuk mewujudkan tujuan negara, yang ketiganya menunjukkan hubungan integral yang saling berkait kelindan sebagai triangel of basic state consensus, yaitu Pancasila sebagai dasar falsafah negara (philosofische grondslag), UUD 1945 sebagai hukum dasar negara, dan Haluan Negara sebagai pedoman kebijakan dasar negara. Unsur penting dari Haluan Negara itu adalah adanya prinsip-prinsip direktif sebagai pedoman yang mengarahkan kebijakan negara atau sebagai kaidah penuntun dalam menjabarkan nilai-nilai Pancasila dan pasal-pasal konstitusi ke dalam kebijakan pembangunan negara dan peraturan perundang-undangan.